A model to guide patient selection when managing ureteric stones with shockwave lithotripsy. (July 2020) - Hemmant, Joshua; Young, Graham; Pournaras, Christos; Foster, Emma; Chow, Karyee
Introduction: The aim of this study was to create a model based upon significant prognostic factors to guide patient selection for shockwave lithotripsy. Patients and methods: We identified 150 patients attending for shockwave lithotripsy for ureteric stones between October 2010–February 2016. Data was collected retrospectively from electronic case notes and radiological images. All patients were treated with an on-site Storz Modulith SLX-F2 lithotripter. A model was created using computer software 'R'. Results: One hundred and thirty-three patients were treated and 66% of those were deemed radiologically stone-free with shockwave lithotripsy. Four factors were found to be independently statistically significant with regards to stone-free status; age ( p =0.003), Hounsfield units ( p =0.002), prior nephrostomy insertion ( p =0.022) or prior stent insertion ( p =0.002). Our resulting model is:Probability of Success = 1 / ( 1 + Exp ( - x ) ) x = 6 . 601 - ( 0 . 043 * Age ) - ( 0 . 004 * [ Hounsfield Units ] ) - ( 1 . 694 * [ Has Neph ] ) - ( 2 . 761 * [ Has Stent ] ) Discussion and conclusions: Our shockwave lithotripsy success would likely increase with improved patient selection. Age appears to be a novel significant factor in stone passage. This is an interesting observation worthy of further study given ageing populations in the developed world. The model will require further validation in order to confirm our findings, however the results have proven very encouraging. Level of evidence: 2c